Manajemen Peserta Didik MTs Laboratorium UINSU - Syafira Syafira; Tasya Zuraira; Amar Khairi Ahmad; Indriyani Br. Sitepu; Arif Abdul Gani Lubis; Inom Nasution; Maryono Maryono (CV. Alim's Publishing, 2023)
The preparation and control of all student-related activities, from their arrival through their departure from a madrasa or educational institution, constitutes student management. When implementing instructional activities at madrasas, student management activities are a crucial component that must be taken into consideration. It has been adopted in the management of students at MTs Lab UINSU, but there are still some students who are not disciplined in respecting the regulations that have been introduced in madrasas, which is causing issues in the management of students. The goal of this study was to learn more about the descriptive qualitative field research approach that MTs Lab UINSU utilizes to supervise its students. It was done to gather data.